Cinema and authenticity: anxieties in the making of historical film*. Issue 2 (1st September 2016) - Lees, Dominic
ABSTRACT: The practice of representing history on film brings the filmmaker into collision with a cluster of concerns around the authentic. While recent articles have considered the historical documentary and historical dramatisation, I seek to extend the debate into narrative fiction film set in historical periods. In this article, I discuss conflicting conceptions of authenticity. Through my own practice-as-research, I examine the decision-making within the preproduction of a historical drama (my short film, The Burning, 2016) in order to demonstrate the ways in which contradictory concepts of authenticity can coexist within a historical film project.